Economic Analysis of EU Strengthened Packaging Waste Recycling Targets - BECCARELLO, Massimo; DI FOGGIA, Giacomo (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The Circular Economy package may contribute to economic growth with new job creation, added value, reduced greenhouse gas emissions and administrative burden. Focusing on higher materials recycling target, this paper appraises the economic implications. The hypothesis that higher recycling targets are associated with positive effects on job creation, production and added value net of the increasing management costs is confirmed. Although limited to Italy and in the light of its packaging waste management system the results suggest positive implications in these free domain.  It is argued though that the path towards a greener and more circular economy needs a sound regulatory framework in order to make the transition towards a circular economy smoother.